Carboxihemoglobinemia e metahemoglobinemia em anestesia geral inalatória com sevoflurano em circuito semifechado com baixo fluxo de gases frescos - Leonardo Homem de Faria Martins (2017)
Carbon monoxide (CO) is a colorless and odorless gas, which has affinity about 250 times by hemoglobin than oxygen (O2), which enables hemoglobin dysfunction with loss of the transport and release of O2 to tissues during anesthesia and clinical effects ranging from headache to cardiovascular shock. May be CO production when inhaled anesthetics and absorber anesthetic circuit carbon dioxide interact, especiallyin anesthesia with low fresh gas flow (FGF), which provides increased anesthetic saving, less environmental contamination and preservation of moisture and heat of the patient's airway in mechanical ventilation. The presence of methemoglobin (MetHb) is associated clinically with use of prilocaine, nitrates and MetHb reductase enzyme deficiency. This study evaluated the variation of the concentration of carboxyhemoglobin(COHb) and MetHb sequentially during the operative time for elective surgery in 100 patients under inhalation anesthesia with sevoflurane, divided into 2 groups: low FGF and high FGF. Two arterial blood samples were collected for analysis. The first sample was drawn immediately after induction of anesthesia immediately before administration of sevoflurane. The second sample was taken immediately before the discontinuation of inhaled agent, still maintaining the predetermined FGF. In these study, there was a difference between the final value of COHb between the groups, with real growth of 0.25% in the low-flow group and reduction of 0.16% in the high-flux group (p <0.0001). There was a positive correlation of 0.31 with low FGF statistically significant. No change has occurred in the values of MetHb or in clinical parameters in per or in the immediate postoperative period. It is concluded that the use of low FGF in anesthesia with sevoflurane provides elevated COHb statistically significant, but without clinical rebound, corroborating the use of this technique.